Prolonged Kidney Ischemia-Reperfusion Injury Associates with Inflammation, Vascular Remodelling, and Myofibroblast Formation - Nur Arfian*; Hilma Kholida Ats-tsani; Pratiwi Indah Sayekti; Dwina Agrila Lakabela; Amelia Amelia; Toni Febriyanto; Hana Rutyana Putri Antonio; Dian Prasetyo Wibisono; Dwi Cahyani Ratna Sari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Prolonged kidney ischemia-reperfusion injury (IRI) is the important risk factor for leading to chronic kidney disease (CKD). Persistent hypoxia and inflammation are considered as the main pathogenesis of chronic injury, followed by myofibroblast expansion and fibrosis process. Tubular injury, cell proliferation, and vasoconstriction, as acute compensatory responses, are restored in chronic phase. The aim of the study was to investigate the relation between inflammation, vascular remodeling, and myofibroblast formation as response to ischemia injury after prolonged kidney ischemia-reperfusion (I/R). Fifteen male Swiss mice aged 3-4 months were used as kidney I/R injury model after bilateral pedicle renal clamping. Rats were divided into 3 groups with five rats in each group i.e. control group (sham operation/SO), acute I/R model (IR1), and chronic I/R model (IR12). PAS staining was used for scoring tubular injury. Fibrosis was assessed using sirius red and a-SMA immunostaining for myofibroblast expansion. PCNA and CD68 immunostaining were used for identifying cell proliferation and macrophage infiltration. RT-PCR was conducted for assessing MCP-1, HIF-1a, and ppET-1 expression, which were quantified using ImageJ software. Data were analyzed using one way ANOVA and Kruskal-Wallis test with significance level of p<0.05. Significantly increase of tubular injury score (p<0.001) and PCNA positive cell (p<0.001) in IR1 group compared to SO were observed, otherwise HIF-1a of IR12 enhanced (p<0.05). Macrophage cell count (p<0.01) and MCP-1 expression (p<0.05), were significantly increase in IR1 and IR12 injury, compared to SO. Wall thickness of arteries was significantly increase (p<0.05) as well as decrease of vascular lumen area (p<0.05), followed by enhancement of ppET-1 expression (p<0.01) in IR1 group and restored significantly (p<0.05) in IR12 group. Fibrosis fraction-area and myofibroblast expansion were significantly increase gradually from IR1 to IR12 injury (p<0.01). In conclusion, prolonged kidney I/R injury induces the sustainability of hypoxia and inflammatory response, which promotes myofibroblast formation, and decrease the response of vascular remodelling.